Perilaku konsumsi masyarakat terhadap pangan berbahan dasar sagu di Pekanbaru, Indonesia - Rini Nizar; Anto Ariyanto; Asgami Putri (Jurnal Ilmiah Pertanian, 2021)
Riau Province makes sago (Metroxylon sp) one of the alternative sources of gluten-free food. Sago has been processed into food ingredients ranging from traditional with local wisdom approaches to modern. The processing of sago was recorded to produce hundreds of food menu creations. However, from various kinds of processed foods made from sago, this is still constrained by the low level of consumption of sago-based foods. It is presumably because the community still has many food sources as a substitute for rice, such as cassava, corn, and others. If viewed from the potential of raw materials for sago owned by Riau Province, sago can be the primary source of food diversification, one of the steps to reduce dependence on the primary carbohydrate source obtained from rice. Therefore, analysis is needed to determine what factors influence a consumer's decision to consume food products made from sago. The method used in this study was a survey method by accidental random sampling. The research model used was a logistic regression model. The survey location was performed in Pekanbaru as the capital city of Riau Province. Testing on the significance of the model was carried out using the Likelihood Ratio Test and the Wald Test. The results showed that the processed sago that consumers often consume was sago noodles (54%). As a local food, the sago was determined mainly by the processed and the price of sago. Therefore, to maintain the sustainability of sago, the government needs to play a role.